Development of a digital twin for collaborative decision‐making, based on a multi‐agent system: application to prescriptive maintenance. (3rd February 2022) - Lorente, Quentin; Villeneuve, Eric; Merlo, Christophe; Boy, Guy André; Thermy, François
Abstract: The fourth industrial revolution involves more complexity. This research effort focuses on decision‐making in helicopter engine maintenance activities. Such a decision‐making task is difficult and relies on a variety of experts who only have partial knowledge and incomplete situation awareness, due to the great diversity of everyday operational practices. In this paper, we propose a digital twin multi‐agent approach to collaborative decision‐making in prescriptive maintenance.